Genome-wide association study of agronomical and root-related traits in spring barley collection grown under field conditions - Ogrodowicz, Piotr; Mikołajczak, Krzysztof; Kempa, Michał; Mokrzycka, Monika; Krajewski, Paweł; Kuczyńska, Anetta (Frontiers in Plant Science, 2023)
The root system is a key component for plant survival and productivity. In particular, under stress conditions, developing plants with a better root architecture can ensure productivity. By performing a genome-wide association study (GWAS), we identified several associations underlying the variations occurring in root- and yield-related traits in response to natural variations in soil moisture. We report the results of the GWAS based on both individual single-nucleotide polymorphism markers and linkage disequilibrium (LD) blocks of markers for 11 phenotypic traits that are related to plant morphology, grain quality, and root system in a group of spring barley accessions grown under field conditions. In addition, we evaluated the root structure of these accessions using a noninvasive method based on electrical capacitance. The results showed the importance of two LD-based blocks on chromosomes 2H and 7H in the expression of root architecture and yield-related traits. Furthermore, this study provides new insights into the role played by root traits in the yield performance of barley plants grown under natural conditions where daily variations in soil moisture are noted.